The Recharge Ketrampilan Guru Melalui PKM Analisis Kualitas Butir Soal Menggunakan Iteman di SMA - Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana; Damianus Ndamung; Marambaawang; Asniyanti Loda Hamu Meha; Adisthy Bunga Here; Vindri Vivien Adinda Kornelis (JPM: Jurnal Pengabdian Masyarakat, 2024)
This community service is motivated by the belief that analyzing questions takes a long time and takes a lot of energy. This is because. The analysis process is often carried out manually using Ms Excel. Teachers have not been trained to analyze the quality of questions using assisted applications. Analysis of the quality of the questions in question includes the level of difficulty, distinguishing power and distractor function of the questions. For this reason, this activity was carried out to recharge teachers' skills in analyzing the quality of question items using the computer program Iteman at Payeti Christian High School. The method used consists of 2 stages, namely: analyzing the quality of question items from the results of the National Examination for class 12 students and providing direct training for teachers to analyze using by the computer program Iteman Version 4.3. Apart from that, open interviews were also conducted and questionnaires were distributed for satisfaction surveys. The output of this activity is a question bank which can be used as a reference for creating subsequent questions and can develop higher quality question items. This activity provides benefits or good impacts for teachers, namely that they are increasingly trained in using the computer program Iteman so that the process of analyzing the quality of the items can be carried out quickly, looks effective and efficient. It can be concluded that this activity is very good to continue and can even be implemented in other schools that need it.